Cash transfer is positively associated with better dietary outcomes – Evidence from a phone survey among women with children less than two years in six states of India - Neupane, Sumanta; Nguyen, Phuong Hong; Avula, Rasmi (International Food Policy Research Institute, 2022)
Introduction • Women’s diet is one of the immediate determinants of maternal and child nutrition Objectives • Examine dietary intake of women with children <2 years of age • Examine inequity in dietary intake by wealth status • Assess the role of food or cash transfers in maternal diet diversity Methods • Data came from a phone survey of 6,227 women in six states of India. • Dietary intake was assessed using the diet quality questionnaire which was then recategorized to calculate score for food diversity, consumption of healthy and unhealthy foods, and minimum diet diversity (MDD) for women. • Inequity in dietary intake was examined using wealth quintiles • Association between food and cash transfer on maternal diet was examined using multivariate regression analysis controlling for maternal, child, households' factors and state fixed effects.